Anti-obesity Properties of Phytochemicals: Highlighting their Molecular Mechanisms against Obesity - Poulios, Efthymios; Koukounari, Stergia; Psara, Evmorfia; Vasios, Georgios K.; Sakarikou, Christina; Giaginis, Constantinos (Current Medicinal Chemistry, 2024)
Obesity is a complex, chronic and inflammatory disease that affects more than one-third of the world’s population, leading to a higher incidence of diabetes, dyslipidemia, metabolic syndrome, cardiovascular diseases, and some types of cancer. Several phytochemicals are used as flavoring and aromatic compounds, also exerting many benefits for public health. This study aims to summarize and scrutinize the beneficial effects of the most important phytochemicals against obesity. Systematic research of the current international literature was carried out in the most accurate scientific databases, e.g., Pubmed, Scopus, Web of Science and Google Scholar, using a set of critical and representative keywords, such as phytochemicals, obesity, metabolism, metabolic syndrome, etc. Several studies unraveled the potential positive effects of phytochemicals such as berberine, carvacrol, curcumin, quercetin, resveratrol, thymol, etc., against obesity and metabolic disorders. Mechanisms of action include inhibition of adipocyte differentiation, browning of the white adipose tissue, inhibition of enzymes such as lipase and amylase, suppression of inflammation, improvement of the gut microbiota, and downregulation of obesity-inducing genes. In conclusion, multiple bioactive compounds-phytochemicals exert many beneficial effects against obesity. Future molecular and clinical studies must be performed to unravel the multiple molecular mechanisms and anti-obesity activities of these naturally occurring bioactive compounds.
Keywords: molecular mechanisms